Vasorelaxant effects of Crataegus pentagyna: Links with arginase inhibition and phenolic profile. (24th April 2020) - Bujor, Alexandra; Miron, Anca; Luca, Simon Vlad; Skalicka-Wozniak, Krystyna; Silion, Mihaela; Trifan, Adriana; Girard, Corine; Demougeot, Céline; Totoson, Perle
Abstract: Ethnopharmacological relevance: Crataegus leaves, flowers and fruits have been traditionally used to improve blood circulation, numerous preclinical and clinical studies supporting the cardiovascular benefits of Crataegus preparations. In this respect, there is very limited data on Crataegus pentagyna ; in addition, the chemical profile of this species is still incompletely elucidated. Aim of the study: The objective of this study was to examine the cardiovascular benefits of Crataegus pentagyna Waldst. et Kit. ex Willd. (small-flowered black hawthorn, Rosaceae) extracts (leaf, flower and fruit ethyl acetate extracts) and the underlying mechanisms. We hypothesized that C. pentagyna extracts might exert vasodilatory effects and inhibit arginase activity due, in large part, to their polyphenolic constituents. Materials and methods: C. pentagyna extracts induced-relaxation and the mechanisms involved were studied ex vivo in isolated aortic rings from Sprague-Dawley rats. The inhibitory effects on bovine liver arginase I were assessed by an in vitro assay. Metabolite profiling of C. pentagyna extracts was performed and the most endothelium- and nitric oxide synthase-dependent; flower extract additionally reduced Ca 2+ entry and, to a lesser extent, Ca 2+ release from the sarcoplasmic reticulum. C. pentagyna proved to be an important source of arginase inhibitors with potential benefits in endothelial dysfunction that remains to be explored. Graphical abstract: Image 1